2002
DOI: 10.1099/00221287-148-12-3873
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the fadD33 gene in the growth of Mycobacterium tuberculosis in the liver of BALB/c mice

Abstract: The potential pathogenic role of Mycobacterium tuberculosis H37Rv fadD33, a gene encoding an acyl-CoA synthase that is underexpressed in the attenuated strain H37Ra, was investigated. In a first approach, fadD33 was cloned and expressed in strain H37Ra to restore gene expression and fadD33-complemented bacteria were used to investigate whether fadD33 might confer any growth advantage to M. tuberculosis H37Ra in an infection model of BALB/c mice. No differences were found in the growth rates of M. tuberculosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…In this study, we have identified a genetic locus involved in the assembly of mycobactins, which we propose to annotate as mbt-2. Interestingly, several genes from the mbt-2 cluster were earlier demonstrated to be essential for the growth of mycobacteria (16,17). Our studies here delineate the biochemical functions of all these genes.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…In this study, we have identified a genetic locus involved in the assembly of mycobactins, which we propose to annotate as mbt-2. Interestingly, several genes from the mbt-2 cluster were earlier demonstrated to be essential for the growth of mycobacteria (16,17). Our studies here delineate the biochemical functions of all these genes.…”
mentioning
confidence: 66%
“…One such interesting cluster contains proteins (FadD33 and FadE14) that showed distinct homology to proteins involved in lipid metabolism. The disruption of fadD33 gene in M. tuberculosis H37Rv had earlier suggested the important role of the gene product in mycobacterial virulence by supporting its replication in the liver (17). Computational analysis of FadD33 protein indicated that this protein was homologous to the newly discovered fatty acyl-AMP ligase (FAAL) proteins from mycobacteria (19).…”
mentioning
confidence: 93%
“…Most notable are those described in Enterobacter cloacae and Haemophilus influenzae (112,135). An orthologue of the FACS FadD has been experimentally defined in Mycobacterium tuberculosis (113).…”
Section: Genetic Foundations Of Fatty Acid Transportmentioning
confidence: 99%
“…Mutants which cannot synthesize cyclopropane synthetase (pcaA), isocitrate lyase enzyme (icl), or phospholipases had reduced survival in mice (14,27,39). Likewise, leucine and pantothenate auxotrophic mutants (⌬leuD, ⌬panD) as well as mutants which had defects in lipid or iron metabolism were all attenuated in SCID or normal mice to various degrees (16,25,40,44). Disruption of genes for nonenzyme proteins has also identified additional functional mutants.…”
mentioning
confidence: 99%